Research on Minimum Miscible Pressure Between Crude Oil and Supercritical Carbon Dioxide System in Ultra-Low Permeability Reservoir by the Long-Slim-Tube Experiment Method - Fan, Guangjuan; Zhao, Yuejun; Zhang, Xiaodan; Li, Yilin; Chen, Hao (Frontiers in Earth Science, 2021)
Carbon dioxide (CO2) injection has become an important technology to enhance oil recovery in ultra-low permeability reservoirs. Compared with other CO2 flooding technologies, CO2 miscible flooding has a better development effect, and the minimum miscible pressure (MMP) is a key parameter to realize miscible flooding. Therefore, it is very important to accurately predict the MMP. The prediction methods of MMP generally include laboratory experiment method and theoretical calculation method. In this study, a long-slim-tube displacement experiment method was used to determine the MMP in the study area, and the experimental temperature and pressure were consistent with those under reservoir conditions. The research results show that the recovery ratio increased gradually with the increase of experimental pressure, but the increase amplitude gradually decreased. According to the relation curve between crude oil recovery ratio and experimental displacement pressure, when the experimental pressure was larger than 29.6 MPa, the recovery ratio did not increase significantly with the increase of displacement pressure, which indicates that the interfacial tension between crude oil and CO2 disappeared under this pressure and they reached a miscible state. It is speculated that the MMP between crude oil and CO2 system in the study area predicted by the long-slim-tube displacement experiment method was 29.6 MPa. The results of this study help to realize miscible flooding in ultra-low permeability reservoirs and thus enhance oil recovery.